Potential For Banana Agrotourism Development in Pakuan, Narmada, West Lombok, Indonesia: Potensi Pengembangan Agrowisata Pisang di Pakuan, Narmada, Lombok Barat, Indonesia - Cicilia, Siska; Romansyah, Erni (Indonesian Journal of Tropical Biology, 2025)
Banana agrotourism in Pakuan Village, Narmada, West Lombok, serves as a strategic instrument for sustainable rural development by integrating agricultural potential with tourism experiences. This study aims to identify internal and external environmental factors to formulate comprehensive development strategies for banana-based agrotourism. Using a quantitative descriptive method with a case study approach, data were collected from 10 key respondents selected via purposive sampling and analyzed using IFE, EFE, IE, and SWOT matrices. Theoretically, this research enriches the discourse on community-based tourism by providing an empirical model for aligning local agricultural commodities with strategic management frameworks. The results indicate that the agrotourism development occupies a growth and build position, characterized by strong internal resource availability and favorable external opportunities despite infrastructural limitations. As a result, the study recommends an aggressive expansion strategy focused on diversifying processed banana products, upgrading tourism facilities through stakeholder partnerships, and intensifying digital marketing efforts